Which country has the world's best health care? - Emanuel, Ezekiel J., 1957- (PublicAffairs, 2020)
"The preeminent doctor and bioethicist Ezekiel Emanuel is repeatedly asked one question: Which country has the best healthcare? He set off to find an answer. The US spends more than any other nation, nearly $4 trillion, on healthcare. Yet, for all that expense, the US is not ranked #1 -- not even close. In Which Country Has the World's Best Healthcare? Ezekiel Emanuel profiles 11 of the world's healthcare systems in pursuit of the best or at least where excellence can be found. Using a unique comparative structure, the book allows healthcare professionals, patients, and policymakers alike to know which systems perform well, and why, and which face endemic problems. From Taiwan to Germany, Australia to Switzerland, the most inventive healthcare providers tackle a global set of challenges -- in pursuit of the best healthcare in the world."--Book jacket.